Assessment of Knowledge Competency Achievement - Jannah, Siti Sri Fattul Jannah; Eka Widyanti (Kirana Publisher (KNPub), 2024)
Assessment in education has an important role in measuring and supporting students' overall learning achievement. The background to this research is the need to understand how various assessment techniques can be used to obtain a comprehensive picture of student abilities. The aim of this research is to identify and evaluate the effectiveness of various assessment techniques and instruments in education. The research methods used include literature studies and literature analysis related to assessment techniques, including formative, summative assessments, written tests, observations, interviews, and portfolios. The research results show that using various assessment techniques simultaneously can provide a deeper understanding of students' learning achievements and support the holistic development of their skills and competencies. In conclusion, comprehensive and diverse assessments not only measure learning outcomes but also serve as a means to improve the learning process itself.